STUDI KRITIS HISTORIS KOMUNIKASI MENTERI PENERANGAN HARMOKO DENGAN PERS DI ERA ORDE BARU - Panggih Sundoro (Jurnal Pustaka Komunikasi, 2018)
The study the historical-critical communication study of Information Minister of Harmoko and press in New Order Era is an interesting phenomenon particularly during the rule of the New Order government. The struggle for freedom of the press is the symbol of press struggle like in the American Revolution. It also prevails for Indonesian press with its major figures. They were successful to insert the freedom of the press in some articles of the 1945 Constitution. After the independence, however, Indonesian press did not get the freedom instantly. In the New Order Era, the press was under the control of the government of President Suharto through the hand of Information Minister Harmoko during his three periods of ministerial office. Finally, Harmoko, a former journalist, occupied the position of Chairman of MPR RI (People's Consultative Assembly of Republic of Indonesia). Harmoko's communication skill to control the Indonesian press were carried out through some measures, i.e. the establishment of Indonesian Journalists' Association (PWI), the control of Indonesian Press Board and The Indonesian News Publishers' Association (SPS) as well as the appointment of chief editors as the Golkar party officials. Harmoko also adopted the Press Law Number 21 of 1982 and issued Press Publication Permit (SIUPP). The study applies qualitative research constructivist paradigm. It occurs in the past because it uses historical approach and public relations theories, mass media/press communication, sociological communication, psychological communication and political communication.